The Effect of Knowledge Management on Innovation and Organizational Performance in the field of Application and Game Development - Budiprayitno, Simon (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2020)
This research examines the effect of knowledge management on innovation and organizational performance (Case Study on Creative Industries in the field of Application and Game Development in Malang Raya). Looking at the existing phenomena clearly shows that most creative industries still show a lot of room for improvement regarding their innovation and business performance and the lack of application of knowledge management in creative industries compared to large organizations. Data collection methods in this study include field research that is by collecting necessary data (primary data) from a sample using a questionnaire instrument that explains and tests hypotheses (explanatory) and uses literature studies derived from literature and scientific journals. The results of this study are that management knowledge has a significant effect on innovation and performance. Innovation has a significant effect on performance and that knowledge management has a significant effect on performance through innovation Changes in performance are primarily determined by the high ability of innovation due to the creative industry players have increased the ability in knowledge management.